Desafios da bioprospecç\~ao no Brasil - Nilo Luiz Saccaro Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The aim of this work is to provide an overview of the challenges of bioprospecting in Brazil by discussing the successes and difficulties encountered in the quest for it development. Several challenges arise: to improve the legislation for access to genetic resources and sharing of benefits; to invest in regional research infrastructure; to incorporate a concern with the use of biodiversity in industrial and regional development policies; to encourage the legal participation of private capital; to repress the illegal appropriation of information and biological material; and to press international bodies to regulate the patenting of products arising from biodiversity. Overcome it mean an important contribution to Brazilian economic development, coupled with the reduction of regional inequalities and environmental preservation.
Keywords: Q01; 330